Electric Energy Production from Cotton Residues Using Stirling Engine - ZOGBOCHI, Victor; CHETANGNY, Patrice Koffi; HOUNDEDAKO, SOSSOU; CHAMAGNE, Didier; BARBIER, Gérald; VIANOU, COKOU ANTOINE (My University, 2019)
This work designs and simulate a system based on free-piston Stirling engine and a brushless doubly fed induction generator to adapt it to local electrical energy production by using cotton waste. The thermal model of the Stirling machine is based on the polytropic expansion / compression process of the working gas to include a number of parameters and to facilitate numerical simulation. A special emphasis was made on the thermal model of the generator to evaluate the impact of heat on the hot part of the block on its performance. The heat source is a synthesis gas obtained from the processing of cotton residues with a gasification rate of 70%.Experimental and simulation results have shown that this machine consuming 0.7 ton of gas i.e. 1 ton of cotton waste is capable of producing a maximum power of 1.5 kW.
Keywords: Stirling engines; Cotton; Generators; Thermal conductivity; Thermal resistance